An overview of ordered mesoporous material SBA-15: synthesis, functionalization and application in oxidation reactions - Chaudhary V.; Sharma S. (My University, 2025)
Ordered mesoporous materials are attracting wide concern because of their applications in the field of catalysis, adsorption, separations, drug delivery systems and gas sensors owing of their extremely high surface area combined with well-defined pore structures with narrow pore size distributions. Various mesoporous materials such as MCM-41, MCM-48, SBA-15 and SBA-16 have been reported in past two decades. Synthesis of mesoporous materials involves the concept of aggregation of surfactants as structure directing agents under acidic or basic conditions. The dimensions of these mesopores can be obtained by type of surfactant, auxiliary chemicals and synthesis conditions. At present, SBA-15 has attracted more attention among different mesoporous silica structures due to their desirable properties such as thick pore wall and hexagonal mesopores (4–12 nm), high surface area, ease of synthesis and functionalization and high thermal and mechanical stability. In last few years, great effort has been made on the development of various methods for the synthesis of mesoporous materials as support for oxidation reactions. The aim of this review article is to focus mainly on mesoporous SBA-15 together with its application as support for various oxidation reactions. © 2016, Springer Science+Business Media New York.